The Digital Learning Revolution: AI-Powered Adaptive Learning in PGSD Lectures - Hertati, Elvani (LPPM STIKI Malang, 2024)
The development of digital technology has significantly impacted education, including PGSD (Primary School Teacher Education) lectures. AI-powered adaptive learning offers vast potential to revolutionize digital learning in PGSD, particularly in the course on Digital Learning. This study aims to explore the use of AI-powered adaptive learning in the context of fifth-semester PGSD students enrolled in Digital Learning courses for elementary schools. This research employs a qualitative approach with a case study method. Data were collected through observations, in-depth interviews with lecturers and students, and document analysis. Data were analyzed thematically to identify the benefits, challenges, and effective strategies for implementing AI-powered adaptive learning. The findings reveal that AI-powered adaptive learning has significant potential to enhance the effectiveness of digital learning in PGSD lectures. This system can provide personalized learning tailored to the needs and abilities of each student. It also boosts learning motivation, fosters independence, and optimizes study time. However, the study also highlights several challenges, such as resource availability, technology access, and lecturers' readiness to implement this system. This research recommends that universities consider integrating AI-powered adaptive learning as an integral part of digital learning in PGSD lectures. It also serves as a reference for developing strategies and policies that support the effective and sustainable implementation of AI-powered adaptive learning in higher education.